ANALYSIS OF HUMOUR IN TV SERIES FRIENDS AND ITS TRANSLATION INTO LITHUANIAN - Korostenskienė, Julija; Pakrosnytė, Miglė (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*289.15px); top: calc(var(--scale-factor)*84.02px); font-size: calc(var(--scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.3668);" role="presentation">http://<span dir="ltr" style="left: calc(var(--scale-factor)*312.91px); top: calc(var(--scale-factor)*84.02px); font-size: calc(var(--scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.11626);" role="presentation">dx.doi.org/10.1515/sm-<span dir="ltr" style="left: calc(var(--scale-factor)*397.90px); top: calc(var(--scale-factor)*84.02px); font-size: calc(var(--scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.06264);" role="presentation">2017-<span dir="ltr" style="left: calc(var(--scale-factor)*418.90px); top: calc(var(--scale-factor)*84.02px); font-size: calc(var(--scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.05634);" role="presentation">0017 The present study examines humour in the tenth season of the TV sitcomFriends and its translation from English into Lithuanian. With humour often believed to beculture-specific, humour translation presents a notorious issue in translation practice, asjocular content in the target language is often criticised for being poor and vague. Groundedin Raskin’s (1985) theory of verbal humour and adopting Schjoldager’s (2008) inventory oftranslation microstrategies, the article examines the components and mechanisms ofhumour in the source language and analyses the strategies applied to humour translation,focusing on whether the intended humorous effect is preserved in the target language. Thearticle also seeks to establish to what extent humour as used in Friends is culturedependent.The study was conducted at two levels. First, we briefly presented the essenceof Raskin’s model of humour, which centres around the notions of script and incongruity,and later applied it to the selected series to identify and analyse the data in the sourcelanguage. We then supplemented the findings with the identification of jokes in the targetlanguage and assessment of translation microstrategies employed in rendering humorousinstances in Lithuanian. The findings of the study are believed to further the theoretical andpractical domains of translation from English into Lithuanian in particular and, more broadly,contribute to the discussion on the culture-specific worldview.